Pendekatan Konseling Humanistik dalam Meningkatkan Keterampilan Sosial Anak dengan Disabilitas Sosial: Literature Review - Diana Zumrotus Sa’aadah; Sella Kinasih; Rista Fahera (Program Studi Bimbingan Konseling Islam, Fakultas Tarbiyah Dan Ilmu Keguruan, Institut Ummul Quro Al-Islami Bogor, 2026)
This article is a literature review that aims to analyze the role of a humanistic counseling approach in improving the social skills of children with social disabilities. The humanistic approach focuses on developing self-potential, unconditional positive regard, empathy, and congruence. Children with social disabilities often experience barriers to social interaction, low self-esteem, and difficulty understanding social norms. Through a humanistic counseling approach, counselors strive to help children understand and accept themselves so they can interact more adaptively in their social environment. The study results indicate that humanistic counseling is effective in developing self-awareness, empathy, interpersonal communication, and independence in children with social disabilities. The article concludes with practical implications for counselors, teachers, and parents in supporting a client-centered counseling process.